Pitfalls and guide lines in the transition to object oriented software design methodologies - Jansen van Rensburg, Miranda (My University, 1998)
Due to the dynamic nature of the software engineering industry there is a constant move towards new strategies for solving design problems. More specifically there is a move towards Object Oriented (OO) methodologies, presumably because of the various advantages offered in terms of maintainability, and reuse of code produced this way. As with various other aspects of the software industry there are however also problems encountered in this transition and lessons to be learned from the experience of companies who have already performed this change. This research report investigates possible guidelines for companies who are currently contemplating a change to the OO software design methodologies, by covering a collection of issues one should know about prior to this change. It also summarises the problems faced in the transition so far, the reasons for these problems and suggests possible solutions. Lastly it also investigates new trends in the OO arena. The emphasis is on South African companies and projects. The results obtained are compared with results obtained overseas to find out what the differences and similarities are. Areas of concern are also identified, where theoreticians' views have been ignored, and both South African and overeeas companies have not implemented any of the suggestions made.
A research report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering.
Keywords: Computer software -- Development.; Software engineering -- Methodology.